Predictors of treatment outcome in an effectiveness trial of cognitive behavioral therapy for children with anxiety disorders. (January 2016) - Wergeland, Gro Janne H.; Fjermestad, Krister W.; Marin, Carla E.; Bjelland, Ingvar; Haugland, Bente Storm Mowatt; Silverman, Wendy K.; Öst, Lars-Göran; Bjaastad, Jon Fauskanger; Oeding, Kristin; Havik, Odd E.; Heiervang, Einar R.
Abstract: A substantial number of children with anxiety disorders do not improve following cognitive behavioral therapy (CBT). Recent effectiveness studies have found poorer outcome for CBT programs than what is typically found in efficacy studies. The present study examined predictors of treatment outcome among 181 children (aged 8–15 years), with separation anxiety, social phobia, or generalized anxiety disorder, who participated in a randomized, controlled effectiveness trial of a 10-session CBT program in community clinics. Potential predictors included baseline demographic, child, and parent factors. Outcomes were as follows: a) remission from all inclusion anxiety disorders; b) remission from the primary anxiety disorder; and c) child- and parent-rated reduction of anxiety symptoms at post-treatment and at 1-year follow-up. The most consistent findings across outcome measures and informants were that child-rated anxiety symptoms, functional impairment, a primary diagnosis of social phobia or separation anxiety disorder, and parent internalizing symptoms predicted poorer outcome at post-treatment. Child-rated anxiety symptoms, lower family social class, lower pretreatment child motivation, and parent internalizing symptoms predicted poorer outcome at 1-year follow-up. These results suggest that anxious children with more severe problems, and children of parents with elevated internalizing symptom levels, may be in need of modified, additional, or alternative interventions to achieve a positive treatment outcome. Highlights: Knowledge of predictors of outcome is important for adapting CBT in community clinics. Anxiety symptom severity and impairment predicted poorer outcome. A primary social phobia or separation anxiety disorder predicted poorer outcome. Parent internalizing symptoms predicted poorer outcome. Children with these characteristics may need adapted CBT treatment.